Role of "Rehabilitation Outcome Measures" in Rehabilitation Medical Services and Development Status - Shanli YANG; Shanjia CHEN; Jing TAO; Cai JIANG; Guanli XIE; Lidian CHEN (康复学报)
To search in the database of "Pubmed" and "CNKI" for the Chinese and English literatures related to Rehabilitation Outcome Measures in recent 10 years and to expound Rehabilitation Outcome Measures, it is a new rehabilitation medicine concept and the representativeness meaning of rehabilitation medicine environment, as well as to review the domestic and foreign research progress of Rehabilitation Outcome Measure in rehabilitation medicine field, and aim to provide some understanding and promote development of theoretical concepts and clinical implications of Rehabilitation Outcome Measure for domestic rehabilitation and health medicine specialists.